2020
DOI: 10.1002/mbo3.1063
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation in Acinetobacter baumannii was inhibited by PAβN while it had no association with antibiotic resistance

Abstract: This study was conducted to investigate the relationship between Acinetobacter baumannii biofilm formation and antibiotic resistance. Furthermore, the effects of PAβN, a potential efflux pump inhibitor, on A. baumannii biofilm formation and dispersion were tested, and the gene expression levels of efflux pumps were determined to study the mechanisms. A total of 92 A. baumannii isolates from infected patients were collected and identified by multiplex PCR. The antimicrobial susceptibility of A. baumannii clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
1
17
1
Order By: Relevance
“…Similar correlations between IPM and LVX were recently described (El-Din et al, 2021), this may be attributed to the various impacts that resulted from a mutation at one or a few genetic loci (Adamus-Bialek et al, 2013). Our isolates exhibited much higher frequency (100%) of biofilm production as opposed to A. baumannii clinical isolates (70.1%) lately investigated from Egypt (Asaad et al, 2021), Iran (70.6%) (Ranjbar and Farahani, 2019), and China (54%) (Chen et al, 2020). Several studies linked high frequency of biofilm formation in A. baumannii with extended survival and resistance to external stresses such as limited nutrients and dehydration (Badave and Kulkarni, 2015;Sung, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Similar correlations between IPM and LVX were recently described (El-Din et al, 2021), this may be attributed to the various impacts that resulted from a mutation at one or a few genetic loci (Adamus-Bialek et al, 2013). Our isolates exhibited much higher frequency (100%) of biofilm production as opposed to A. baumannii clinical isolates (70.1%) lately investigated from Egypt (Asaad et al, 2021), Iran (70.6%) (Ranjbar and Farahani, 2019), and China (54%) (Chen et al, 2020). Several studies linked high frequency of biofilm formation in A. baumannii with extended survival and resistance to external stresses such as limited nutrients and dehydration (Badave and Kulkarni, 2015;Sung, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…In a clinical A. baumannii isolate, AdeFGH efflux pump was overexpressed along with abaI in sessile condition, suggesting its role in the efflux of substrates required for biofilm formation ( He et al., 2015 ). Targeting RND efflux pump with its inhibitor Phenylalanine-arginine beta-naphthylamide (PaβN) significantly reduced the biofilm formation ability of A. baumannii and weakly eradicated preformed biofilm ( Chen et al., 2020 ).…”
Section: Biofilm Formation and Biofilm Associated Infectionsmentioning
confidence: 99%
“…[15], Ranjbar and Farahani, [16], and Chen et al [17], who found that 76.9%, 70.6% and 54% of clinical A. baumannii isolates produced biofilms respectively.…”
Section: Discussionmentioning
confidence: 99%